IDENTITY AND TRANSFORMATION: A POSTCOLONIAL STUDY OF MOHSIN HAMID’S THE LAST WHITE MAN (2022) - Syyeda Wafa Zainab Kazmi; Haroon Sarfraz; Sidra Noreen (International Journal of Contemporary Issues in Social Sciences, 2024)
The study examines Mohsin Hamid's "The Last White Man" to explore identity in a postcolonial context, focusing on the novel's treatment of racial transformation and its effects on personal and collective identities. It interrogates how the interplay between physical and societal transformations within the narrative engages with postcolonial themes of race, identity, and belonging. Drawing on the theoretical frameworks of Frantz Fanon, with his focus on the psychological impacts of colonialism on identity, and Homi K. Bhabha's concepts of hybridity and the "third space," the study aims to understand how Hamid's speculative narrative questions and reshapes conventional postcolonial themes of otherness and sameness. The significance of this study lies in its capacity to shed light on the complexities of postcolonial identity formation, challenging the rigidity of racial categories and societal norms that enforce these constructions. The conclusion highlights the novel's contribution to postcolonial discourse, urging a reevaluation of identity beyond binary racial distinctions, towards a more inclusive understanding of human connection.